1973
DOI: 10.1620/tjem.111.71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Furosemide Administration and Upright Position on Plasma Renin Activity and Angiotensin II in Hypertension

Abstract: Both plasma renin activity and angiotensin ‡U during recumbency measured by radioimmuno assay, were normal in essential hypertension, chronic glomerulonephritis and bilateral renal artery stenosis, definitely low in primary aldosteronism, and high in unilateral renal artery stenosis. In normal subjects upright posture and furosemide administration induced an elevation in plasma renin activity; which correlated directly with the elevation in angiotensin ‡U. In general, the increase in plasma renin activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Reports show that in the human the presence of hypertension does not mean that PRA is going to be beyond the normal range (Fukuchi et al, 1973;Johnston et al, 1973). As observed in this study, PRA or Angiotensin I values were not influenced by blood pressure or body weight.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Reports show that in the human the presence of hypertension does not mean that PRA is going to be beyond the normal range (Fukuchi et al, 1973;Johnston et al, 1973). As observed in this study, PRA or Angiotensin I values were not influenced by blood pressure or body weight.…”
Section: Resultssupporting
confidence: 70%
“…Fukuchi et al (1973) reported a range of .13 to 3.00 ng/ml/hr for normal humans and for people with malignant hypertension .72 to 10.0 ng/ml/hr. Kosunen and Pakarinen (1976) reported normal human values to be 2.42 ng/ml/hr, and it was shown that the PRA increased by 108% immediately after exercise (running).…”
Section: Resultsmentioning
confidence: 99%